The Transition from an Individualistic and Internalist Model to a Social and Collaborative One in Higher Education - Piedra García, Luis Ángel (2010)
The following document will address the issue of the processes of transition from an university education abundant in internal, individualistic and competitive arguments towards one which may be more social and collaborative that might tell us which one is the natural way of teaching and learning in terms of our own species. In this article we make a general analysis of some key elements in the analogical university education parallel to the rejection of the idea that we are mainly informationprocessing machines.